Investigation of the Effectiveness of Laser Therapy in Myofascial Pain Syndrome - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: Myofascial pain syndrome (MPS) is a common chronic pain condition affecting the musculoskeletal system and there are various treatment options. In this study, we investigated the efficacy of laser therapy in MPS. Methods: Sixty patients (35 female, 25 male) diagnosed with MPS due to trigger points in the upper trapezius muscle were included in our study. The patient files were evaluated in two groups of 30 people, each waiting in line with the diagnosis of MPS (n=30) and those who were not yet treated with the same diagnosis (n=30). LED gallium-aluminium-arsenide 1.6 W, 808 nm wavelength diode laser therapy and exercise therapy were applied to the treatment group for 12 minutes once a day for 10 days, while the control group received only exercise therapy. The level of pain at rest and during activity was measured by visual analog scale (VAS)

pain intensity and sensitivity was measured by algometric measurement and 0-5 Likert scale

the functional status of the patients was evaluated using the Neck Pain and Disability scale (NPADS) and the quality of life of the patients using the Short Form-36 (SF-36). All these tests were recorded before the treatment, after the treatment and at the 1st month after the treatment in both groups, and the effectiveness of the treatment was examined. Results: The mean age of the cases was 33.4 +/- 10.5 in the treatment group and 36.1 +/- 10.6 in the control group. There was no significant difference between the demographic data of the patients in the control group and laser group. The 15th and 30th day VAS resting scores, VAS activity scores, 0-5 Likert scale and NPADS scores were found to be significantly lower in the treatment group compared to the control group. Algometric measurement score and SF-36 score on the 15th and 30th days were found to be significantly higher in the treatment group than in the control group. Conclusion: In this study, it is seen that conventional laser therapy application in the treatment of MPS is effective on pain complaints at rest and during activity, besides, it decreases the trigger point sensitivity and increases the pressure pain threshold on the trigger point.
Keywords: Exercise; laser therapy; myofascial pain syndrome; TRIGGER POINTS; RELIABILITY; EFFICACY; MANAGEMENT; INTERRATER; MECHANISMS; ULTRASOUND; NECK